2013 IEEE Conference on Computer Vision and Pattern Recognition 2013
DOI: 10.1109/cvpr.2013.271
|View full text |Cite
|
Sign up to set email alerts
|

Salient Object Detection: A Discriminative Regional Feature Integration Approach

Abstract: Abstract-Salient object detection has been attracting a lot of interest, and recently various heuristic computational models have been designed. In this paper, we formulate saliency map computation as a regression problem. Our method, which is based on multi-level image segmentation, utilizes the supervised learning approach to map the regional feature vector to a saliency score. Saliency scores across multiple layers are finally fused to produce the saliency map. The contributions lie in two-fold. One is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
797
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,037 publications
(806 citation statements)
references
References 59 publications
5
797
2
2
Order By: Relevance
“…To evaluate the performance of our saliency model, we choose 10 state-ofthe-art saliency models: DRFI, IDRFI, BL, CGVS, DW, HDCT, MS, PR-GL, RRWR and SPMP to compare with our model [10,[28][29][30][31][32][33][34][35][36]. In experiments, we utilize 2 metrics for quantitative performance evaluations including Precision and Recall curve(PR) and F-measure.…”
Section: Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the performance of our saliency model, we choose 10 state-ofthe-art saliency models: DRFI, IDRFI, BL, CGVS, DW, HDCT, MS, PR-GL, RRWR and SPMP to compare with our model [10,[28][29][30][31][32][33][34][35][36]. In experiments, we utilize 2 metrics for quantitative performance evaluations including Precision and Recall curve(PR) and F-measure.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…In most traditional methods, the salient objects were derived by the features extracted from pixels or regions, images were usually decomposed into several superpixel regions and final saliency maps consisted of these regions with their saliency scores [7][8][9][10]. The performance of these models rely on the segmentation methods and the selection of the feature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this work we focus on unsupervised salient object detection. While supervised approaches, such as those in [45] and [36], have the potential of finding more accurate results, their performance depends on the training process followed and the data that has been exploited for training. Recent works have also indicated that unsupervised saliency detection approaches can compete (or even outperform) supervised methods [43].…”
Section: Probabilistic Saliency Estimationmentioning
confidence: 99%
“…DRFI [45] was also ranked as one of the top methods in the study; however, it is a supervised method and, hence, it is not included in our comparisons. The saliency maps for the above algorithms were downloaded from the website [30] related to the study in [43].…”
Section: Comparison With the State-of-the-artmentioning
confidence: 99%
“…Recently, numerous bottom-up saliency detection methods have been proposed,which prefer to generate the saliency map by utilizing the boundary information.In [12],the contrast against image boundary is used as a new regional feature vector to characterize the background.In [14],a more robust boundary-based measure is proposed,which takes the spatial layout of image patches into consideration. [15] uses the four boundaries of an image as background cues to get foreground queries via manifold ranking(MR).…”
Section: Related Workmentioning
confidence: 99%